The Influence Of Transformational Leadership, Work Environment And Workloads On Intention To Leave And Employee Performance - Puspita, Vida Indira; Mujanah, Siti; Nugroho, Mulyanto (Economic and Bussiness Faculty, Dr Soetomo University, 2020)
This research aims to analyze the influence of transformational leadership, work environment, and workloads on an intention to leave and employee performance in Bank Jatim Headquarters. The sample in this study is 84 employees of Bank Jatim headquarters using simple random sampling. Method of data collection using survey technique with questioners as instruments and methods of data analysis using PLS (Partial Least Square). The results of this study indicate that transformational leadership applied in the company has a significant effect on the intention to leave employees. However, the work environment and Workload gave to employees considerable impact does not affect the intention to leave of employees. Otherwise, transformational leadership does not significantly influence employee performance, and work environment, workloads, and intention to leave employees have a significant effect on employee performance.